Sustained employability of workers in a production environment: design of a stepped wedge trial to evaluate effectiveness and cost-benefit of the POSE program - van Holland Berry J; de Boer Michiel R; Brouwer Sandra; Soer Remko; Reneman Michiel F (BMC, 2012)
Abstract Background Sustained employability and health are generating awareness of employers in an aging and more complex work force. To meet these needs, employers may offer their employees health surveillance programs, to increase opportunities to work on health and sustained employability. However, evidence for these health surveillance programs is lacking. The FLESH study (Functional Labour Evaluation for Sustained Health and employment) was developed to evaluate a comprehensive workers' health promotion program on its effectiveness, cost-benefit, and process of the intervention. Methods The study is designed as a cluster randomised stepped wedge trial with randomisation at company plant level and is carried out in a large meat processing company. Every contracted employee is offered the opportunity to participate in the POSE program (Promotion Of Sustained Employability). The main goals of the POSE program are 1) providing employee's insight into their current employability and health status, 2) offering opportunities to improve employability and decrease health risks and 3) improving employability and health sustainably in order to keep them healthy at work. The program consists of a broad assessment followed by a counselling session and, if needed, a tailored intervention. Measurements will be performed at baseline and will be followed up at 20, 40, 60, 80, 106 and 132 weeks. The primary outcome measures are work ability, productivity and absenteeism. Secondary outcomes include health status, vitality, and psychosocial workload. A cost-benefit study will be conducted from the employers' perspective. A process evaluation will be conducted and the satisfaction of employer and employees with the program will be assessed. Discussion This study provides information on the effectiveness of the POSE program on sustained employment. When the program proves to be effective, employees benefit by improved work ability, and health. Employers benefit from healthier employees, reduced sick leave (costs) and higher productivity. The study can expose key elements for a successful implementation and execution of the POSE program and may serve as an example to other companies inside and outside the industry. Trial registration The trial is registered at the Dutch Trial Register (http://www.trialregister.nl): NTR3445